Operationalization of teledebriefing in health education: scoping review - Bernardinelli, Fabiana Cristina Pires (2025)
Introduction: Telesimulation is characterized as an innovative educational technology capable of reaching remote, hard-to-access locations. However, despite its importance, one of its stages, teledebriefing, still lacks sufficient scientific exploration. Objective: To map scientific literature on the operationalization of teledebriefing aimed at teaching students and health professionals. Materials and methods: This is a scoping review based on the recommendations of the Joanna Briggs Institute and Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews: Checklist and Explanation, conducted in April 2025 in 13 databases. Results: Twenty-nine studies were identified as the final sample. Two categories were identified: practice and elements for the implementation of teledebriefing in teaching and learning in health, and benefits versus challenges of teledebriefing. Conclusion: In short, the operationalization of teledebriefing mainly involved the need for teletransmission resources, the presence of a trained facilitator/teledebriefer, the determination of a teledebriefing method and duration. The main benefit of  teledebriefing is its contribution to improving the learner’s self-confidence, motivation, decision-making, and critical thinking. A key challenge, however, is the teledebriefer’s limited ability to observe the reactions of remote participants during the discussion.